The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.15761/imm.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Role of nutritional factor menaquinone-7 in bone homeostasis and osteoporosis prevention

Abstract: Bone homeostasis is mainly regulated by osteoblasts, osteocytes and osteoclasts. Osteoblasts promote bone formation and osteoclasts stimulate bone resorption. Bone loss with aging is due to decreased osteoblastic bone formation and increased osteoclastic bone resorption. Bone loss with various pathophysiologic states leads to osteoporosis. Nutrition and functional food factors may play a role in the prevention of bone loss. Menaquinone-7 (MK-7), a kind of vitamin K 2 , has been shown to reveal stimulatory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Osteoblast DNA levels have been associated with OC expression, osteoprotegerin, NFκB ligand (RANKL), and RANK ligand promoter genes facilitated by vitamin K [74,75]. Furthermore, the vitamin K family participates in sphingolipids synthesis, in addition to their structural role, sphingolipids take part in proliferation, differentiation, and intercellular recognition activities of neurons [76]. Vitamin D3 cannot affect proliferation on its own, but does support osteoblast differentiation, as demonstrated by increased expression of typical markers such as runt-related transcription factor 2 (RUNX2), type I collagen, alkaline phosphatase, and OC [77,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblast DNA levels have been associated with OC expression, osteoprotegerin, NFκB ligand (RANKL), and RANK ligand promoter genes facilitated by vitamin K [74,75]. Furthermore, the vitamin K family participates in sphingolipids synthesis, in addition to their structural role, sphingolipids take part in proliferation, differentiation, and intercellular recognition activities of neurons [76]. Vitamin D3 cannot affect proliferation on its own, but does support osteoblast differentiation, as demonstrated by increased expression of typical markers such as runt-related transcription factor 2 (RUNX2), type I collagen, alkaline phosphatase, and OC [77,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Researching the cis / trans isomers of MK-6 and MK-7 is very important from a biological point of view because only the trans forms of vitamins K 1 and K 2 manifest biological activity. The cis or cis / trans forms of menaquinones do not manifest such activity or manifest it at a very low level [ 5 , 9 , 28 , 36 ], this has been proven in the case of cis vitamin K 1 (Lowenthal and Rivera [ 25 ]) and mixtures of the cis / trans MK-6 isomers [ 37 ]. Based on these publications, it can be concluded that the cis or cis/trans isomers are chemical impurities of MK-7 and MK-6.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K 1 is a cofactor of γ-glutamylcarboxylase that modifies hepatic blood coagulation factors. Vitamin K 2 has a higher affinity for extrahepatic γ-glutamylcarboxylase, modifying proteins such as osteocalcin, matrix Gla-protein or growth arrest specific gene 6 protein [ 7 , 8 , 9 ]. Vitamin K forms differ not only in target tissues but also in biological activity, as long-chain menaquinines show greater activity compared to short-chain ones due to the longer half-life in the blood [ 4 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular functions in osteoclastic and osteoblastic cells are performed by various proteins, whose expression is regulated by K2-7 ( Yamaguchi, 2014 ). Osteocalcin produced by osteoblasts binds to calcium present in blood circulation and leads it to the bone matrix.…”
Section: Vitamin K2-7 and Associated Diseasesmentioning
confidence: 99%